United Nations Primer for Development: Reply - Frankel, S. Herbert (Quarterly Journal of Economics, 1953)
Journal Article United Nations Primer for Development: Reply Get access S. Herbert Frankel S. Herbert Frankel Nuffield College, Oxford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 67, Issue 2, May 1953, Pages 280–285, https://doi.org/10.2307/1885339 Published: 01 May 1953